The Effect of Brand Image, Store Atmosphere, and Visual Merchandising on Purchase Decision in Miniso Plaza Medan Fair - T Teviana (Jurnal Manajemen Bisnis Eka Prasetya, 2022)
Characteristics of Miniso that relate to aesthetic trend in society and Miniso succeed to affect purchase decision of customers. The purpose of this research is to find the effect of Brand Image, Store Atmosphere and Visual Merchandising on Purchase Decision in Miniso Plaza Medan Fair. The population in this research is entire customers of Miniso Plaza Medan Fair in 2020 with the amount of samples are 100 respondents. Method of data collection is using the questionnaires. Based on partial test obtained the result that brand image, store atmosphere, and visual merchandising severally have positive and significant effect on purchase decision. Beside that simultaneous test obtained that brand image, store atmosphere, and visual merchandising simultaneously have positive and significant effect on purchase decision. The result of coefficient determination test is that R square value is 0,84 which means brand image, store atmosphere, and visual merchandising contribute the effect on purchase decision by 84% and the rest is affected by other factors that not included in this research. The conclusion is there are a positive and significant affect among brand image, store atmosphere, and visual merchandising on purchase decision in Miniso Plaza Medan Fair.